Kiat Bisnis Halal Dan Pengelolaan Modal Pada Generasi Z - Reviandani, Wasti; Akhiruddin, Anita (JURNAL PENGABDIAN MANAJEMEN, 2025)
The fast-paced digital era is one of the reasons why Generation Z is entering the business world. Various creativity, wide access to social media and inspiration from various successful young entrepreneurs increasingly support young people in pursuing business. Gen Z is currently known as a generation that is close to technological developments, easy to get along with and often uses social media. Generation Z also often has a fairly luxurious lifestyle such as traveling, eating, drinking coffee or dressing style and using the latest smartphones and much more. Generation Z’s creativity in halal business can create new products or services, further develop existing services or products, choose and develop industry names, marketing is mainly done online, for example through social media and online shopping, company design must. combine Paths that make it more attractive and diversify products. The purpose of the service is to explain in more detail about halal businesses that can be done and their development as well as financial management that must be started early. Socialization was carried out face-to-face with students and teachers of SMA Muhammadiyah 10 Gresik. Along with presenting the material, the implementing team showed a video that had been made by the implementing team on Youtube related to business activities and basic financial management. The final result is that participants can understand how to start a simple halal business and understand how to separate personal finances and business finances.